2017
DOI: 10.21608/mnj.2017.149622
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fatigue and Functional Status of the Elderly Patients on Hemodialysis

Abstract: Background: Patient safety has become an area of interest in many countries. One of the most important types of patient safety is pressure ulcers that constitute an important sanitary problem that daily affects the patients and the health care systems. Several studies have indicated that nurses' knowledge, perception and practices about pressure ulcer (PU) prevention are inadequate. Therefore, the aim of this study is to assess nurses' knowledge, perception and practices regarding pressure ulcer at the Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This may be due to people living in rural areas are less able to maintain healthy life style and do not have access to high quality prevention, early detection, and treatment services in which there is limited access to health care. This finding in line with Abd Rabouh (2015) [20] in Egypt and Stanifer et al, 2014 [21] who found that ESRD more prelevant in rural area than urban area. This finding not agree with a study done in Egypt by El Shahed, Sharf, El Sebaee & Roshdy (2013) [22] who reported that about two third of their studied patients were living in an urban area.…”
Section: Figure (2)supporting
confidence: 84%
“…This may be due to people living in rural areas are less able to maintain healthy life style and do not have access to high quality prevention, early detection, and treatment services in which there is limited access to health care. This finding in line with Abd Rabouh (2015) [20] in Egypt and Stanifer et al, 2014 [21] who found that ESRD more prelevant in rural area than urban area. This finding not agree with a study done in Egypt by El Shahed, Sharf, El Sebaee & Roshdy (2013) [22] who reported that about two third of their studied patients were living in an urban area.…”
Section: Figure (2)supporting
confidence: 84%
“…Functional status had a significant negative correlation with fatigue among patients undergoing CAPD, implying that individuals with higher functional status experience less fatigue. While a prior study discovered a correlation between fatigue and functional status in older patients undergoing hemodialysis (Abd-Rabouh et al, 2017 ), an alternative interpretation suggests that reduced capability to perform routine daily functions could elevate the risk of experiencing high fatigue levels.…”
Section: Discussionmentioning
confidence: 98%
“…Fatigue has adverse effects across various dimensions of life among patients with CAPD. For instance, patients who experience high levels of fatigue engage in fewer daily activities and become more dependent on others (Abd-Rabouh et al, 2017 ). Several patients have expressed that fatigue significantly impacts their emotional well-being and social participation.…”
Section: Introductionmentioning
confidence: 99%